Novel Strategies for Biodegradation and Detoxification of Mycotoxins (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Mycotoxins contamination is a continuing global problem that severely affects animal health and performance, and further threatens food safety. The industry's common aspiration is to eliminate feed mycotoxins contamination and control their hazards. In recent years, animal mycotoxicosis has occurred frequently all over the world, which has brought huge economic losses to the agriculture industry. The potential damage caused by mycotoxins-induced decreased disease resistance in animals and food safety problems in human health is incalculable. There is a long way to go to prevent mycotoxins hazards. Biodegradation is a promising strategy to eliminate mycotoxins as it can transform mycotoxins into nontoxic or less toxic metabolites under mild conditions, retaining the sensory quality and nutritional value of agricultural commodities. Moreover, animals have a certain ability to detoxify mycotoxins, and some bioactive substances, such as lipoic acid, sporoderm-broken spores of Ganoderma lucidum, and quercetin, can improve the detoxification ability of animals to reduce the toxic effects of mycotoxins. This reprint aimed to gather contributions of original research or reviews related to novel strategies for biodegradation and detoxification of mycotoxins. Topics of interest will include novel mycotoxin-degrading microorganisms and enzymes, fermentation technology to reduce the mycotoxin content in cereal products, studies on alleviating the mycotoxicosis of livestock by the addition of bioactive substances or mycotoxin biodegradation agents, and any preliminary research that promotes progress in this field.